What influences Hb fetal production in adulthood? - Carrocini, Gisele Cristine de Souza [UNESP]; Zamaro, Paula Juliana Antoniazzo [UNESP]; Bonini-Domingos, Claudia Regina [UNESP] (Associação Brasileira de Hematologia e Hemoterapia e daSociedade Brasileira de Transplante de Medula Óssea, 2011)
Human hemoglobin genes are located in α and β globin gene clusters in chromosomes 16 and 11, respectively. Different types of hemoglobin are synthesized according to the stage of development with fetal hemoglobin (α2γ2) (Hb F) being the main hemoglobin in the fetal period. After birth, there is a reduction (to about 1%) in Hb F levels and adult hemoglobin, Hb A (2α2β2), increases to more than 96% of total hemoglobin. However, some genetic conditions whether linked to the β-globin gene cluster or not are associated with high Hb F levels in adults. Among those linked to β-globin are hereditary persistence of fetal hemoglobin, delta-beta thalassemia (δβ-Thalassemia) and the XmnI polymorphism (-158 C > T). Other polymorphisms not related to β-globin gene cluster are known to influence the γ-globin gene expression in adulthood. The most relevant polymorphisms that increase concentrations of Hb F are the HMIP locus on chromosome 6, the BCL11A locus on chromosome 2, the Xp22.2 region of the X chromosome and the 8q region on chromosome 8. Findings from our research group studying genetic factors involved in γ-globin gene regulation in adults without anemia in the northwestern region of São Paulo State showed that high Hb F levels are influenced by the presence of hereditary persistence of fetal hemoglobin mutations and the XmnI polymorphism, suggesting that both genetic alterations characterize the molecular basis of the evaluated population.
Keywords: Fetal hemoglobin; Genetic polymorphism; gamma-Globins